Navigating the complex care landscape: Addressing challenges and advancing adult care frameworks for individuals with cerebral palsy - Jensine’ Clark; Cristina Sarmiento; Jessica Sanders; Lauren Wang; Lauren Fetsko; Unoma Akamagwuna (Health Care Transitions)
Despite cerebral palsy (CP) being the most common motor disability in childhood, there are more adults living with CP than children. The necessitates a systematic approach to the care of adults with CP. This perspective piece presents the complex nature of a lifespan approach to the care of a childhood-onset disability. We share the multidisciplinary considerations from a primary care model to address chronic health conditions and preventive care. We also present a care model with an emphasis on Neurology and Neurodevelopmental Disability with its implications for adults with CP. Finally, we advocate for a care model that encompasses a biopsychosocial approach to treatments and interventions with essential elements that include the adult perspective.